Analysis Of Farming And Factors Affecting The Income Of Carrot Farming In Air Duku Village, Selupu Rejang Sub-District, Rejang Lebong District - Indah Fitria (University of Prof. Dr. Hazairin, SH, 2023)
The development of the production of an agricultural commodity must be in line with the development of the price of the commodity in question. This is because the high or low income of farmers is determined by the amount of production sold and the commodity prices received by farmers at harvest time. The success of a farming business can be seen from the income received by farmers. Therefore, increasing the profit of carrot farmers can be achieved through improving the allocation of the use of production factors in carrot farming, so that production efficiency can be increased. Seeing the high amount of carrot production in Selupu Rejang District, especially Air Duku Village, the author is interested in examining how high the income level of carrot farming is and analyzing what factors affect carrot farming income in Air Duku Village where this village is included in the Selupu Rejang District area which is become a commodity producer of carrots in Rejang Lebong Regency. Based on the analysis carried out, the following results show that the average income of carrot farming in Air Duku Village, Selupu Rejang District, Rejang Lebong Regency is Rp. 3,928,380.80,-/Ut. This means that farmers' income can cover all costs incurred during farming production activities. Land area, age, education level and number of family dependents simultaneously have a significant effect on carrot farming income and partially which have a significant effect are land area, age and number of family dependents.